Digging into the Technological Dimension of Environmental Productivity - Filippo Belloc; Edilio Valentini (Fondazione Eni Enrico Mattei (FEEM), 2022)
We propose a mixture model approach to identify locally optimal technologies and to dissect environmental productivity (output produced per unit of emission) into a technological and a managerial component. For a large sample of plants covered by the EU ETS, we find that the share of plants adopting the frontier technology is about 21%. We also find that the average output gains that plants could reach by adopting optimal technologies and managerial practices are 75% and 80% respectively. These results remain qualitatively similar after addressing endogeneity of emissions. Finally, we match EU ETS data with balance-sheet data on parent companies and find that better environmental technologies tend to be adopted by larger, listed, multi-plant and international companies, while older firms and firms with higher intangibles assets intensity more commonly show improved environmental management. Our results suggest that existing technologies have large unexploited potentials and deliver important insights for policy.
Keywords: D24; L60; Q54; Q55; 330; Environmental productivity; Emission intensity; Environmental technology; Environmental management